Exploring firm and individual-level determinants of IFRS for SMES adoption in Morocco, a diffusion of innovations' perspective - Issam Benhayoun; Ibtissam Zejjari (Cogent Business & Management, 2024)
This research delves into the adoption dynamics of International Financial Reporting Standards for Small and Medium-sized Entities (IFRS for SMEs) in Morocco, a nation yet to embrace these standards, presenting a distinctive opportunity to scrutinize the challenges of implementation within a developing, pre-adoption milieu. While existing studies have primarily scrutinized post-adoption scenarios through a macroeconomic lens, often neglecting individual and firm-level intricacies, this investigation employs qualitative methodologies such as semi-structured interviews and content analysis to unearth fresh determinants of accounting standards adoption. Insights gleaned from discussions with 12 accounting professionals unveil novel factors like Implementation Modality and Industry Sector, contributing to a more nuanced comprehension of the adoption process at both individual and organizational levels. By shedding light on these micro-level dynamics, this study addresses a notable gap in the literature, augmenting the predominantly country-level analyses of IFRS for SMEs adoption.
Keywords: M400; M410; 650; IFRS; SMEs; adoption; determinants; diffusion of innovation; content analysis; qualitative; emerging economies; developing country